Dual Control High-rise Building for Robuster Earthquake Performance - Fukumoto, Yoshiyuki; Takewaki, Izuru (Frontiers in Built Environment, 2017)
A dual passive control system is proposed for high-rise buildings. Since the proposed system needs a substructure supporting the main building, it is usually used in high-rise residential apartment houses where a parking tower is used as the substructure. This new system consists of a base-isolation system and a building-connection system. While base-isolated buildings and interconnected buildings are effective for special earthquake ground motions, i.e. impulsive type and long-duration type, respectively, a building structure with such system as robust for both-type inputs has never been proposed and investigated in detail. Although some attempts have been conducted, realization of such systems has never been accomplished. In this paper, not only the theoretical background but also the actual installation in a real world is presented in detail. It is shown that the transfer function of the proposed dual building control system possesses lower values in a broader frequency range compared to the conventional building-connection system. This supports the high robustness of the proposed dual building system. It is also shown that the optimal connecting damper quantity providing a lower response of the main frame can be obtained by maximizing the area of energy transfer function which implies the energy absorption of the connecting dampers under an idealized white noise-like input.